Investigating the effect of audio visual materials as warm-up activity in Aviation English courses on students' motivation and participation at high school level - Secer, Sule Y. E.; Sahin, Mehmet; Alci, Bulent (ELSEVIER SCIENCE BV, 2015)
This paper aims to analyze the effects of video use as an audio visual material as warm-up activity on students' motivation and participation in Aviation English courses at high school level in the viewpoint of English instructors. This paper is based on a qualitative study design in which focus group interview is used as the data collection procedure. The participants of the focus group interview are four instructors teaching Aviation English, teaching 10th graders in a state high school. It is a fact that the use of video like the other audio visual aids is a proper ice breaker and motivation tool for teenagers in today's modern world of technology. According to the analysis of the data collected by focus group interview, the findings, revealing the positive effect of video use on students' motivation and participation, are categorized and discussed within the scope of the study. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: video as audio-visual material; warm-up activity; students' attention; motivation; 2ND-LANGUAGE; Education & Educational Research; Social Sciences - Other Topics